Aspects Influencing the Quality of Management of the Community Learning Activity Centers in Banten Province - Ahmad Amarullah (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
This research is aimed at studying aspects influencing the quality of management quality of the Community Learning Activity Centers (Pusat Kegiatan Belajar Masyarakat hencefort called PKBM) in Banten province. The approach used in this research is quantitative, with sampling research model. The aspect covers autonomy, supervision, community participation and leadership Quantitative research takes the distance between the researcher and the object of the study. Quantitative research uses formal, standard and measurable instruments. The research sample is 155 PKBMs spread in the eight districts or cities in Banten Province. The results of this study indicate that; (1) autonomy has a direct and indirect positive effect on the quality of PKBM management; (2) supervision directly and indirectly influence the quality of PKBM management; (3) community participation has a direct and indirect positive impact on the quality of PKBM management; (4) leadership has a direct positive effect on the quality of PKBM management; (5) autonomy has a direct positive effect on PKBM leadership; (6) supervision has a direct positive effect on PKBM leadership; (7) community participation has a direct positive effect on PKBM leadership.DOI: 10.15408/insaniyat.v2i1.6585